STUDYING THE PROBLEM OF SOCIAL ADAPTATION OF STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS - D. Zakirova (Academia Science Repository, 2023)
It is known that at present mentally developed, creatively gifted, inquisitive youth is a huge source of strength that drives the scientific and technological progress of society, which in the future will have to integrate with the world community in all spheres. In this regard, the search for young talented specialists, their correct orientation, the formation of knowledge and skills are one of the highest goals. This article discusses the socio-philosophical problem of improving the effectiveness of education in higher education institutions, as well as the social adaptation of students in higher education institutions.